2015
DOI: 10.1007/s12560-015-9209-1
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extracts of Hibiscus sabdariffa Calyces Decrease Hepatitis A Virus and Human Norovirus Surrogate Titers

Abstract: Hibiscus sabdariffa extract is known to have antioxidant, anti-diabetic, and antimicrobial properties. However, their effects against foodborne viruses are currently unknown. The objective of this study was to determine the antiviral effects of aqueous extracts of H. sabdariffa against human norovirus surrogates (feline calicivirus (FCV-F9) and murine norovirus (MNV-1)) and hepatitis A virus (HAV) at 37 °C over 24 h. Individual viruses (~5 log PFU/ml) were incubated with 40 or 100 mg/ml of aqueous hibiscus ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Statistical analysis was carried out using ANOVA with SAS software (version 9.3, SAS Institute, Cary, NC, USA) and Tukey's test with data obtained from the three replications for each individual treated virus and compared to control untreated virus assayed in duplicate as described in previous studies (Su and D'Souza, 2011;Su and D'Souza 2013;Su et al, 2010a;Su, Howell, and D'Souza 2010b;Joshi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Statistical analysis was carried out using ANOVA with SAS software (version 9.3, SAS Institute, Cary, NC, USA) and Tukey's test with data obtained from the three replications for each individual treated virus and compared to control untreated virus assayed in duplicate as described in previous studies (Su and D'Souza, 2011;Su and D'Souza 2013;Su et al, 2010a;Su, Howell, and D'Souza 2010b;Joshi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis A virus (HAV; strain HM175) and fetal rhesus monkey kidney (FRhK4) cells were provided by our collaborator, Dr. Kalmia Kniel (University of Delaware). As described before, all three host cell lines were maintained using Dulbecco's Modified Eagle's Medium/Ham's F-12 (DMEM-F12; HyClone Laboratories, Logan, UT) containing 10 % heat-inactivated fetal bovine serum (FBS, HyClone Laboratories) and 19 Anti-Anti (Antibiotic-Antimycotic, Invitrogen, Grand Island, NY) at 37°C in an atmosphere containing 5 % CO 2 (Su and D'Souza 2011;Joshi et al 2015).…”
Section: Viruses and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…The powdered dried calyx extracts are used as diet nourishment [12]. It has been demonstrated that aqueous extract of the plant possesses antiviral effect on human norovirus surrogates feline calicivirus-9 (FCV-F9) and murine norovirus (MNV-1) as well as in hepatitis A virus [13]. Hibiscus sabdariffa possesses antioxidant, anti-diabetic and antimicrobial properties [13].…”
Section: Hibiscus Sabdariffa (Calyces)mentioning
confidence: 99%